Deliberation, democracy, and civic forums improving equality and publicity - Karpowitz, Christopher F. 1969- (Cambridge University Press, 2014)
"Innovative forums that integrate citizen deliberation into policy making are revitalizing democracy in many places around the world. Yet controversy abounds over whether these forums ought to be seen as authentic sources of public opinion and how they should fit with existing political institutions. How can civic forums include less powerful citizens and ensure that their perspectives are heard on equal terms with more privileged citizens, officials, and policy experts? How can these fragile institutions communicate citizens' policy preferences effectively and legitimately to the rest of the political system?"--Provided by publisher.